From netrin‐1‐targeted SPECT/CT to internal radiotherapy for management of advanced solid tumors. Issue 4 (6th March 2023) - Kryza, David; Wischhusen, Jennifer; Richaud, Mathieu; Hervieu, Maëva; Sidi Boumedine, Jacqueline; Delcros, Jean‐Guy; Besse, Sophie; Baudier, Thomas; Laval, Pierre‐Alexandre; Breusa, Silvia; Boutault, Erwan; Clermidy, Hugo; et al.
Abstract: Targeted radionuclide therapy is a revolutionary tool for the treatment of highly spread metastatic cancers. Most current approaches rely on the use of vectors to deliver radionuclides to tumor cells, targeting membrane‐bound cancer‐specific moieties. Here, we report the embryonic navigation cue netrin‐1 as an unanticipated target for vectorized radiotherapy. While netrin‐1, known to be re‐expressed in tumoral cells to promote cancer progression, is usually characterized as a diffusible ligand, we demonstrate here that netrin‐1 is actually poorly diffusible and bound to the extracellular matrix. A therapeutic anti‐netrin‐1 monoclonal antibody (NP137) has been preclinically developed and was tested in various clinical trials showing an excellent safety profile. In order to provide a companion test detecting netrin‐1 in solid tumors and allowing the selection of therapy‐eligible patients, we used the clinical‐grade NP137 agent and developed an indium‐111‐NODAGA‐NP137 single photon emission computed tomography (SPECT) contrast agent. NP137‐ 111 In provided specific detection of netrin‐1‐positive tumors with an excellent signal‐to‐noise ratio using SPECT/CT imaging in different mouse models. The high specificity and strong affinity of NP137 paved the way for the generation of lutetium‐177‐DOTA‐NP137, a novel vectorized radiotherapy, which specifically accumulated in netrin‐1‐positive tumors. We demonstrate here, using tumor cell‐engrafted mouse models and a genetically engineered mouse model, that a single systemic injection of NP137‐ 177 Lu provides important antitumor effects and prolonged mouse survival. Together, these data support the view that NP137‐ 111 In and NP137‐ 177 Lu may represent original and unexplored imaging and therapeutic tools against advanced solid cancers. Synopsis: During development, netrin‐1 is released and diffusible in the microenvironment. We showed that in cancer, netrin‐1 accumulates in the extracellular matrix. We used this property to follow its in vivo accumulation by radiolabeling and to target netrin‐1‐expressing tumor cells with radioimmunotherapy. In cancer tissues, netrin‐1 is secreted but not diffusible. Netrin‐1 interacts with many components of the extracellular matrix and accumulates in the tumor intercellular space. Anti‐netrin‐1 monoclonal antibody can be radiolabeled to detect in vivo the presence of netrin‐1 as a diagnostic test. Anti‐netrin‐1 monoclonal antibody can be conjugated with Lutetium 177 to cargo the radioelement and destroy tumor cells in vivo . Abstract : During development, netrin‐1 is released and diffusible in the microenvironment. We showed that in cancer, netrin‐1 accumulates in the extracellular matrix. We used this property to follow its in vivo accumulation by radiolabeling and to target netrin‐1‐expressing tumor cells with radioimmunotherapy.